The The Waste Material’s Development from Panan Pandanus Handicrafts to a New - Creative Material Case Study of Panan Pandanus Product Community Enterprise of Ban Duhun, Trang Provinc - Klinsuwan, Saravudh; Rattanarungsikul, Phuvanart (Journal of Fine and Applied Arts Khon Kaen University, 2023)
This research is Practice-based Research aims to 1) study the guidelines and feasibility of developing waste material from Panan Pandanus handicraft 2) to experiment with developing waste material from Panan pandanus handicraft as a new creative material. The study area is Panan pandanus Product of Ban Duhun Community Enterprise, Trang Province. Data collection by recording experimental data and results in a stepwise manner. Analyze the data from the results of the experiments at different stages. The results showed that digestion of Panan pandanus stripes fibers by soaking in water or brine and using boiling heat made the color of the Panan pandanus stripes fibers slightly weaker, but the fibers were not digested. When experimenting with immersion with sodium hydroxide and soaking it with bleach and then bringing it to a boil makes the color of the lighter, longer immersion time and boiling has the effect of which the fiber will begin to be digested more and more. Waste materials from fiber digestion are used to create new materials into 2 shapes: 1. Sheet style: Using pandanus pulp that is less than 100 grams in A4 size frame causes the material to be broken at some area, but using more than 100 grams of pulp, the sheet material will be thicker. The addition of Sodium Carboxymethyl Cellulose (CMC) to the tissue makes the material tougher and stronger. 2. Three-dimensional form: shaped by hand and use of mold, the resulting material is light weight, rough surface. Continuous development possibilities can develop creative new materials in the form of Panan pandanus paper with various texture characteristics caused by fiber digestion method as well as raising awareness according to the circular economy concept, which emphasizes on the cost-effective use of resources in order for the community to use the guidelines for further development.